In situ base release for pH maintenance can allow shake flasks to better mimic bioreactor performance for CHO cell culture - Maralingannavar, Vishwanathgouda; Shenoy, Bharath R.; Hazarika, Jahnabi; Unnikrishnan, Divya; Prabhu, Anuja; Maity, Sunit; Gadgil, Mugdha (Journal of Chemical Technology & Biotechnology, 2018)
BACKGROUNDShake flasks are widely used for evaluating mammalian cells in suspension. Lack of pH control can contribute to differences in culture performance between them and bioreactors. This study evaluates whether a previously reported in situ base releasing hydrogel (pHmH) to counter pH decrease can enable shake flask cultures to better mimic bioreactor cultures. RESULTSCompared with bioreactor culture, fed-batch cultures of a recombinant Chinese hamster ovary (CHO) cell-line in shake flasks without pHmH showed a decrease in pH to 6.6, accompanied by 40, 60 and 22% lower peak cell density, lactate accumulation, and immunoglobulin G (IgG) titer, respectively. Use of pHmH allowed shake flasks to maintain pH above 6.8 and reduced this difference to 20, 30, and 15%, respectively, thus enabling culture performance in shake flasks to better mimic the bioreactor. IgG glycosylation profiles were similar in identically fed cultures across all three platforms. Application of pHmH hydrogel during clone screening was evaluated by comparing correlation between titers for five recombinant CHO clones in bioreactors and shake flasks with and without pHmH; a higher correlation was found in shake flasks with pHmH than without. CONCLUSIONIn situ base release through hydrogel can allow identically fed fed-batch cultures in shake flasks to better mimic cell growth, lactate accumulation and IgG titers in bioreactors, without additional infrastructure. (c) 2018 Society of Chemical Industry.